2018
DOI: 10.1088/1361-6528/aae283
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical metal/polymer metamaterials of tunable negative Poisson’s ratio fabricated by initiator-integrated 3D printing (i3DP)

Abstract: Metamaterials with artificially designed architectures can achieve unique and even unprecedented physical properties, which show promising applications in actuators, amplifiers and micromechanical controls. An initiator-integrated 3D printing technology (i3DP) was applied in this study to create scalable, metal/polymer meta-mechanical materials, which can gradually achieve negative Poisson's ratio, high strength and ultralow density, as well as high compressive and super-elastic behavior. The i3DP was enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The vast majority of published metamaterials are made out of polymers as they can generally accommodate larger deformations [2,3,16,27,37,[41][42][43]. However, it is important to remember that polymers can exhibit viscoelastic properties that will influence the overall mechanical properties, especially under loading conditions [44].…”
Section: Choice Of Materials Manufacturing Process and Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of published metamaterials are made out of polymers as they can generally accommodate larger deformations [2,3,16,27,37,[41][42][43]. However, it is important to remember that polymers can exhibit viscoelastic properties that will influence the overall mechanical properties, especially under loading conditions [44].…”
Section: Choice Of Materials Manufacturing Process and Manufacturingmentioning
confidence: 99%
“…Metal-polymer composite metamaterials are achieved by polyelectrolyte-brush-assisted electroless plating (ELP) of copper. Etching of the interior polymer structure leads to hollow metallic metamaterials [43].…”
Section: Choice Of Materials Manufacturing Process and Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting an assembly method, Wang et al (2018b) fabricated 3D doublearrow-head NPR foam structure and studied their mechanical properties. By using an initiator-integrated 3D printing technology, Zhang et al (2018) introduced metal/polymer reentrant foams with tunable NPR. Based on a classical re-entrant structure, Chen et al (2018) proposed three kinds of novel lattice foams with NPR, which showed enhanced energy absorption capacity, stiffness, and strength.…”
Section: Introductionmentioning
confidence: 99%
“…According to Li et al [110], the most significant advantage of developing − materials are their potential to be tunable [111][112][113]. This allows for targeted failure strain, elastic modulus, and strength while featuring scalable unit-cells for a wide range of applications [114].…”
Section: Introductionmentioning
confidence: 99%